EFEK BIOCHAR DAN TEH KOMPOS TERHADAP PERTUMBUHAN DAN HASIL SELADA DARAT (Lactuca sativa L) DI TANAH VERTISOL SEMIARID - Arnoldus Klau Berek; Arnoldus Klau Berek; Syprianus Ceunfin; Roberto I.C.O Taolin; Eduardus Yosef Neonbeni; Maksimus Johanes Seran (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2017)
Improving soil and plant productivity in semiarid regions was challenged by the climatic factors such low rain fall and high temperature in addition to limited availability of appropriate agricultural technologies. The objective of this field trial was to assess the effect of biochar and compost tea on the growth of curly leave lettuce grown in a semiarid region of West Timor. Two types of biochars (rice husk and sawdust) in combination with two types of compost teas namely Chromolaena odorata stem and guano at two rates (150 ml/plant and 250 ml/plant) were arranged in a factorial randomized completely block design 3 x 3 x 3 with 4 replicates. Soil parameters such as pH and electrical conductivity, and plant parameters such number of leaves, fresh weight were measured to indicate the treatment effects. The results indicated that soil temperature and soil bulk density were decreased, and soil moisture, soil electrical conductivity, number of leaves, total fresh weight, and root length were increased by added biochars and compost teas. Application of rice husk biochar at 10 t/ha in combination with guano compost tea at 250 ml/plant in increase the lettuce shoot fresh weight almost twice compared to the control. This results could be attributed to the improving soil productivity by added biochars and nutrients supply by the teas.